Modulating effects of vanillic acid on circadian pattern of indices of redox homeostasis in N-Methly-N′-Nitro-N-Nitrosoguanidine induced endometrial carcinoma in rats. Issue 4 (3rd July 2016) - Bhavani, P.; Subramanian, P.; Shanmugapriya, S.
Abstract: The circadian timing system controls drug metabolism and cellular proliferation over the 24-h period through molecular clocks in every cell. Accumulating epidemiological and genetic evidences indicate that the disruption of circadian rhythms might be directly linked to cancer. This study evaluates the effect of vanillic acid on the circadian rhythms of circulatory lipid peroxidation and antioxidant status during N-Methyl-N′-Nitro-N-Nitrosoguanidine (MNNG)-induced endometrial carcinoma in rats. The characteristics of circadian rhythms (acrophase, amplitude and mesor) of lipid peroxidation products – thiobarbituric acid reactive substances (TBARS), lipid hydroperoxides (LOOH) and enzymatic antioxidants like superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and non-enzymatic antioxidants such as reduced glutathione (GSH), vitamins C and E were markedly declined in MNNG-treated rats when compared to other groups. Pre and co-treatment of vanillic acid to MNNG-treated animals significantly increased the mesor and altered amplitudes of antioxidants and significantly decreased the mesor values of TBARS and LOOH. Further, delays in acrophase in MNNG-induced rats were reversed by vanllic acid administration. Thus, oral treatment of vanillic acid results in normalization of the altered rhythms of these indices of redox homeostasis (compared to controls) by its anticarcinogenic, cytoprotective and antioxidant effects.